1970
DOI: 10.3126/jcmsn.v6i1.3595
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility pattern of methicillin-resistant <i>Staphylococcus aureus</i> (MRSA) in CMS-teaching hospital: a preliminary report

Abstract: Aims: Nosocomial infection is a major problem in the world today. Methicillin-resistant Staphylococcus aureus (MRSA) strains, usually resistant to several antibiotics and also intrinsic resistance to ß-lactam antibiotics, shows a particular ability to spread in hospitals and now present in most of the countries. The present study was carried out to investigate the prevalence of MRSA and their rate of resistance to different antistaphylococcal antibiotics. Materials and methods: Between April 2007 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
18
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 9 publications
19
18
3
Order By: Relevance
“…In our study 35.50% of the isolates were found to be MRSA by cefoxitin disc diffusion method, which was comparable with the findings by Kshetry et al (37.6%) [8] and Sanjana et al (39.6%) [25]. But lower prevalence was reported by Subedi and Brahmadathan (15.4%) [26] and Baral et al (26%) [27] and higher prevalence was reported by Khanal and Jha (68%) [16] and Tiwari et al (69.1%) [28].…”
Section: Discussionsupporting
confidence: 91%
“…In our study 35.50% of the isolates were found to be MRSA by cefoxitin disc diffusion method, which was comparable with the findings by Kshetry et al (37.6%) [8] and Sanjana et al (39.6%) [25]. But lower prevalence was reported by Subedi and Brahmadathan (15.4%) [26] and Baral et al (26%) [27] and higher prevalence was reported by Khanal and Jha (68%) [16] and Tiwari et al (69.1%) [28].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of MRSA reported in our study was in accordance with that reported by Subedi and Brahmadathan (15.4%) [19]. However, higher rates were reported by Kshetry et al (37.6%) [6], Sanjana et al (39.6%) [20], Dibah et al (46.3%) [21], and Tiwari et al (69.1%) [22]. In a recent study from Nepal, Adhikari et al also reported higher rate of MRSA in comparison to our study [23].…”
Section: Discussionsupporting
confidence: 91%
“…6(2): 4997-5002. drug resistance of MRSA was highest with Penicillin and Oxacillin (100.0%). These findings are in accordance with those of Sanjana et al, (2010). Current results are attributed to fact that MRSA strains are often resistant to all standard β-lactams, macrolides and aminoglycosides antibacterials (Fang et al, 2016).…”
Section: Conflict Of Interestssupporting
confidence: 84%